2012
DOI: 10.1152/advan.00050.2011
|View full text |Cite
|
Sign up to set email alerts
|

Analytical essay writing: a new activity introduced to a traditional curriculum

Abstract: Medical students following a traditional curriculum get few opportunities to engage in activities such as a literature search, scientific writing, and active and collaborative learning. An analytical essay writing activity (AEWA) in physiology was introduced to first-year students. Each student prepared an essay incorporating new research findings with existing knowledge on a medical topic. Students were expected to study on the topic in detail from textbooks as well as from research publications and write a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 14 publications
2
8
0
1
Order By: Relevance
“…Regarding the type 1 project (infectious disease brochure), many students indicated that they benefited from the selfdirected and cooperative learning inherent in applied writing. A similar point was made in a study (Kommalage, 2012) regarding the values of essay writing by medical students. Furthermore, such writing helps develop communication skills in engaging with the lay public (Dorman et al, 2013).…”
Section: Discussionsupporting
confidence: 65%
“…Regarding the type 1 project (infectious disease brochure), many students indicated that they benefited from the selfdirected and cooperative learning inherent in applied writing. A similar point was made in a study (Kommalage, 2012) regarding the values of essay writing by medical students. Furthermore, such writing helps develop communication skills in engaging with the lay public (Dorman et al, 2013).…”
Section: Discussionsupporting
confidence: 65%
“…As yet, however, curriculum design experts have increasingly turned to more authentic alternatives to foster skills for implementing EBM and research. These include, among others, (extracurricular) research electives, summer studentship programmes, and undergraduate theses [ 2 , 9 11 ].…”
mentioning
confidence: 99%
“…In these assignments, students were supposed to use internet, e-mail, Word processing, presentation software and some other ICT related resources. Results of some of the assignmentshave been reported previously (2) .…”
Section: Discussionmentioning
confidence: 94%
“…Several ICT related assignments were conducted for undergraduates of theMedical Faculty.Most of these assignments were guided self studies using internet resources, short analytical essay writing, student seminars and tutorials which required self study using internetresources (1,2) . In these assignments, students were supposed to use internet, e-mail, Word processing, presentation software and some other ICT related resources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation